FEATURES OF ADDED VALUE TAX CALCULATION IN TAXATION SYSTEM FOR AGRARIAN PRODUCERS - A. M. Tufetulov; T. G. Davletshin; Yu. M. Sinnikova (Russian Journal of Economics and Law)
The article views the issues of applying the taxation system for agrarian producers, as well as problems arising when calculating the added value tax, and some ways of their solution. The authors propose amendments to Tax Code of the RF, to equal enterprises with special taxation regimes, and enterprises with common taxation regime.